Biophysical and structural mechanisms of epilepsy-associated mutations in the S4-S5 Linker of KCNQ2 channels - Inn-Chi Lee; Yen-Yu Yang; Hsueh-Kai Chang; Swee-Hee Wong; Shi-Bing Yang (Channels)
Mutations in KCNQ2 are linked to various neurological disorders, including neonatal-onset epilepsy. The severity of these conditions often correlates with the mutation’s location and the biochemical properties of the altered amino acid side chains. Two mutations affecting aspartate at position 212 (D212) in the S4-S5 linker of KCNQ2 have been identified. Interestingly, while the charge-conserved D212E mutation leads to severe neonatal-onset developmental and epileptic encephalopathy (DEE), the more dramatic substitution to glycine (D212G) results in self-limited familial neonatal epilepsy (SLFNE), a much milder pathology. To elucidate the underlying mechanisms, we performed electrophysiological studies and in silico simulations to investigate these mutations’ biophysical and structural effects. Our findings reveal that the D212E mutation stabilizes the channel in the voltage sensor down-state and destabilizes the up-state, leading to a rightward shift in the voltage-dependent activation curve, slower activation kinetics, and accelerated deactivation kinetics. This disruption in KCNQ2 voltage sensitivity persists even in the more physiologically relevant KCNQ2/3 heterotetrameric channels. In contrast, the D212G mutation primarily destabilizes the up-state, but its impact on voltage sensitivity is significantly reduced in KCNQ2/3 heterotetrameric channels. These findings provide key insights into the biophysical and structural basis of KCNQ2 D212 mutations and their contribution to epilepsy-related symptoms, offering a clearer understanding of how these mutations drive the varied clinical outcomes observed in patients.